Evaluation of Pharmacological Activities of the Leaf Extracts of Antidesma menasu Miq. - P, Dhanya; P, Rama Bhat (International Journal of Scientific Research in Biological Sciences, 2020)
Antidesma menasu is a folklore plant known for its anti-inflammatory and analgesic properties. Folklore practitioners use the leaves of this plant for swelling of body parts, lower back pains, arthritis in humans and swelling of shoulders and udders in animals. Development of a new drug requires pre-clinical studies of crude extracts on animal models. The objective of this study is to screen the drug for its pharmacological activities. Present study reveals anti-microbial, anti-inflammatory and analgesic properties of aqueous and ethanol extracts of Antidesma menasu. It also includes toxicity study, for screening the crude extracts for any adverse effects on animals and comparison of the effectiveness of the drug in corresponding solvents.